ANALISIS PENGARUH STRUKTUR MODAL DAN STRUKTUR AKTIVA TERHADAP PROFITABILITAS (Studi Empiris Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012-2016) - Chairunnisa Chairunnisa; Meri Dwi Anggraini; Sulastri Sulastri (LPPM - STIE SAKTI ALAM KERINCI, 2019)
This study aims to determine the effect of capital structure and asset structure on profitability in property and real estate companies listed on the Indonesia stock exchange (BEI) for the period 2012-2016. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2016, the sample in this study amounted to 22 companies taken using purposive sampling technique. The data analysis method used is descriptive static, multiple linear regression, classic assumption test using normality test, Autocorrelation Test, multicollinearity test, and using partial hypothesis testing (T test) with the help of SPSS 20 for windows program. The results of the study in hypothesis testing with a significance level of 5% (0.05) found that partially the capital structure has a significant effect on profitability, because the level is significant (0,000 <0,05). While the asset structure has no significant effect on profitability with a significant value (0.999> 0.05). Adjusted R2 value of 0.159 can be interpreted that the capital structure and asset structure contribute to 15.9% in explaining profitability and the remaining 84.1% is explained by variables outside of this study.